New genus of dikraneurine leafhopper (Hemiptera: Cicadellidae: Typhlocybinae) from Japan, with description of two new species - Ohara, Naomichi; Hayashi, Masami; Kamitani, Satoshi (Zootaxa, 2019)
A new genus, Stictotettix gen. nov. and two new species of Dikraneurini, S. cleyerae sp. nov. and S. morishimai sp. nov., are described and illustrated, based on the specimens from Japan. This new genus is unique in the male genital features of the aedeagal atrium. The two new species live on pentaphylacacean trees, Cleyera japonica and Eurya japonica, respectively.